Keragaman Fungsi dan Bentuk Spasial Pertanian Kota (Studi Kasus: Pertanian Kota di Jakarta) - Hayuning Anggrahita; Guswandi Guswandi (Jurnal Wilayah dan Lingkungan, 2018)
Urbanization in Jakarta encourages the conversion of agricultural land and other green open spaces into built-up areas. Agriculture sector is being marginalized and its contribution is only 0.1% of the economy of Jakarta. Previous studies showed that regardless of its fewer contribution, Jakarta's agriculture persistence takes place due to single to multiple functional transformations especially from staple food production to diverse functions such as environmental, cultural, property rights protection functions, etc. This study aims to identify agricultural multi-functionality in Jakarta. This research uses descriptive quantitative analysis method which is deepened with qualitative analysis through the interview and scientific photography technique to represent physical and social reality in the field. The results indicate that Jakarta’s agriculture is scattered due to urbanization pressure. In addition, Jakarta's agriculture is transformed through the creation of new urban values which demonstrate the ability of urban agriculture to survive.